Contribution to PNA–RNA Chimera Synthesis: One‐Pot Microwave‐Assisted Ugi Reaction to Obtain Dimeric Building Blocks. Issue 3 (30th December 2016) - Ovadia, Reuben; Mondielli, Clémence; Vasseur, Jean‐Jacques; Baraguey, Carine; Alvarez, Karine
Abstract : We report a solution‐phase synthesis of dimeric PNA–RNA (PNA = peptide nucleic acid) building blocks by using a microwave‐assisted Ugi four‐component reaction. A mixture of a functionalized amine, a carboxymethyl nucleobase, paraformaldehyde, and N 4, 2′‐ O, 3′‐ O ‐tribenzoyl‐5′‐deoxy‐5′‐isocyanocytidine generates the dimeric chimeras in one step. The method is simple, and gives rapid access (5 min) to diversity, as exemplified by the products described here. Abstract : An efficient, one‐step synthesis of chimeric PNA–RNA (PNA = peptide nucleic acid) dimers has been developed. This method, based on a Ugi reaction, gives rapid access to dimeric PNA–RNA building blocks with different sequences.